Teaching Methods and the Integration of Moderation Values in Islamic Religious Education in Schools - Anam, Saeful; Zaman, Vela Shofa Royatuz; Iskandar, Khusnan (Academia Publication, 2023)
This study aimed to examine how Islamic Religious Education (PAI) learning strategies contribute to the instillation of moderation values, particularly in light of the numerous social and religious conflicts in Indonesia. Teaching moderation is a crucial approach to addressing these issues, as it plays a fundamental role in integrating Pancasila values into society. This journal explored PAI teaching methods, their impact on moderation values, and the supporting and inhibiting factors influencing PAI learning strategies. The study was conducted using a qualitative approach with a descriptive study design, utilizing key informant interviews, documentation, and observations for data collection. The findings of this study are expected to provide a comprehensive analysis and practical recommendations to enhance education, particularly in instilling moderation values among students.